Cost-minimized diets for UiTM Perlis students using goal and linear programming / Nur Fatihah Fauzi ... [et al.] - Fauzi, Nur Fatihah; Supardi, Nurul Asyiqin; Alias, Rohana; Shafii, Nor Hayati (Universiti Teknologi MARA, Perlis, 2019)
Humans need to eat good and balanced nutritious diet that provides calories for energy requirements and nutrients for proper growth, repair and maintenance of the body tissue. Today, busy lifestyle habits drastically changed the pattern of eating where students are more likely to have irregular meal times and the cost of food may be expensive for them. Therefore, this study is conducted to find the minimum cost that satisfies the daily nutrient requirements. A linear programming (LP) model and goal programming (GP) model are formulated where the objective function is the total cost of food. Food prices were collected from selected cafés in UiTM Perlis and the recommended daily nutrient intakes of 19-29 years old, male and female were obtained from the Ministry of Health Malaysia. The sample used in this research consists of 10 most frequently consumed food items as decision variables. QM for Windows V5 was used to determine minimum cost that satisfies the nutritional requirements. LP results, the minimum cost for male students is RM9.88 and for female students is RM9.10. Based on the GP results, the cost is RM9.00 for both male and female students. It is evident from the results that GP has achieved the minimum cost and the food basket for male students consists of 410g of rice, 140g of chicken, 42.9g of broccoli and 252.7g of mushroom. Meanwhile, the food basket for female students consists of 429g of rice, 113.4g of chicken, 37.44g of broccoli and 321.3g of mushroom.